PF.15 Expectant Management of Monochorionic Diamniotic Twins with Selective Intrauterine Growth Restriction. (26th April 2013) - Flood, K; Breathnach, FM; McAuliffe, FM; Geary, M; Daly, S; Higgins, JR; Dornan, J; Morrison, JJ; Burke, G; Higgins, S; Dicker, P; Tully, E; et al.
Abstract : We sought to evaluate the outcomes in a cohort of MCDA twins with a diagnosis of selective intra-uterine growth restriction (sIUGR) who were managed expectantly. This prospective multicenter cohort study recruited 1, 028 unselected twin pairs over 2 years in Ireland. Monochorionic twins underwent fortnightly ultrasonographic surveillance from 16 weeks. The defining criterion for sIUGR was an estimated fetal weight less than the 10 th centile in one twin with an appropriately grown co-twin. Details of the prenatal course, delivery timing and perinatal outcomes were recorded. Outcome data were recorded for 100% of the 1, 001 twin pairs that completed the study (n = 200 monochorionic). Five percent (n = 10) of the MCDA twin pregnancies were diagnosed with sIUGR at a median gestation of 30 weeks (range 26 – 35 weeks). AEDF or REDF was identified in two of these cases. The median time interval from diagnosis to delivery was 36.8 days (range 3 – 66 days) at a mean gestation of 34.2 weeks (range 26 – 37.9 weeks). 70% of the affected twins were admitted to the NICU with a mean stay of 19 days. There were no perinatal mortalities recorded. Our findings demonstrated excellent outcomes for our cohort of MCDA twins complicated by selective IUGR. There was no single IUFD and in turn there was no morbidity conferred to the appropriately grown co-twin. Close surveillance with regular ultrasonography and Doppler evaluation was essential and allowed continuation of the majority affected pregnancies to a late gestational age, thereby optimising outcome for both twins.